EFEK SINERGISTIK ASAM URSOLAT TERHADAP AKTIVITAS SITOTOKSIK DOKSORUBISIN PADA SEL KANKER PAYUDARA MCF-7 - , Ibrahim Arifin, Drs. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Breast cancer is one of the most deadly cancers. The main priority of breast cancer treatment is the use of chemotheraupetic agents, especially doxorubicin. However, breast cancer treatment using doxorubicin has potency to generate cardiotoxicity and cancer cell resistance. An approach recently developed to overcome side effects of doxorubicin is to used of combined chemotheraupetic agent (cochemotherapeutic agent), i.e. ursolic acid. The aim of this research is to develop the potency of ursolic acid as cochemotherapeutic agent by observing the cytotoxic effect and cell cycle modulation on MCF-7 breast cancer cell lines. The determination of the cytotoxic activity of ursolic acid and doxorubicin and the combination of them was done using MTT assay to obtain the value of IC50 and CI (Combination Index). The profile of cell cycle is observed using flowcytometry and analyzed using Modfit LT 3.0 program. Ursolic acid had cytotoxic effect on MCF-7 breast cancer cell with IC50 of 37 μM. The combination ursolic acid ½ IC50 (19 μM) and doxorubicin ¼ IC50 (87,5 nM), 1/3 IC50 (116,7 nM), and ½ IC50 (175 nM)